Structural evolution and relative stability of vanadium-doped boron clusters. (2nd November 2022) - Xiang, Zhiyang; Luo, Zhongjie; Bi, Jie; Jin, Siyu; Zhang, Ziqiang; Lu, Cheng
Abstract: Cluster is the intermediate of individual atom and larger agglomeration. The structural evolutions of clusters are critically important to explore the physical properties of bulk solids. Here, we carry out systematic structure predictions of medium-sized vanadium-doped boron clusters by using crystal structure analysis by particle swarm optimization method combined with density function theory calculations. A great deal of low-lying isomers with attractive geometries are discovered, such as the crown-like VB18 − cluster and the drum-like VB20 − cluster. Interestingly, the VB12 − cluster possesses excellently relative stability due to its higher second-order difference and larger highest occupied molecular orbital (HOMO)-lowest unoccupied molecular orbital (LUMO) energy gap. The molecular orbitals (MOs) and adaptive natural density partitioning (AdNDP) analysis indicate that the 3 d orbitals of V atom and the 2 p and 2 s orbitals of B atoms are the primary constituents of the MOs, and the interactions between V and B atoms are the main factor for the robust stabilization of the anionic VB12 − cluster. The present findings advance the understanding of the structural evolution of transition metal doped boron clusters and offer crucial insights for future experiments.